2004
DOI: 10.1038/sj.ijo.0802737
|View full text |Cite
|
Sign up to set email alerts
|

Is serum leptin related to physical function and is it modifiable through weight loss and exercise in older adults with knee osteoarthritis?

Abstract: OBJECTIVE:To determine the effect of weight loss and exercise interventions on serum leptin and to investigate the relationship of physical function and osteoarthritis (OA) severity with serum leptin in older overweight and obese adults with knee OA. In addition, the study examined if serum leptin predicts weight loss. DESIGN: Longitudinal, controlled clinical trial of weight loss and exercise interventions. SUBJECTS: Community dwelling, older, overweight and obese adults (n ¼ 316; 460 years of age; body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 54 publications
2
47
0
1
Order By: Relevance
“…While Iwamoto reported that serum leptin concentration might be related to increases in body weight and total fat mass in postmenopausal women with knee OA, 27 Miller reported that decreases in serum leptin could explain why weight loss improved physical function and symptoms in patients with knee OA. 28 de Boer documented a distinctly higher serum leptin level in end-stage knee OA patients as compared with controls, 5 and we also reported that hip JSN was associated with serum levels of leptin in older adults. 10 In contrast, Yusuf reported that serum leptin level was positively correlated with BMI but was not associated with progression of hand OA, while serum adiponectin was associated with reduced progression of hand OA over time.…”
Section: Discussionmentioning
confidence: 82%
“…While Iwamoto reported that serum leptin concentration might be related to increases in body weight and total fat mass in postmenopausal women with knee OA, 27 Miller reported that decreases in serum leptin could explain why weight loss improved physical function and symptoms in patients with knee OA. 28 de Boer documented a distinctly higher serum leptin level in end-stage knee OA patients as compared with controls, 5 and we also reported that hip JSN was associated with serum levels of leptin in older adults. 10 In contrast, Yusuf reported that serum leptin level was positively correlated with BMI but was not associated with progression of hand OA, while serum adiponectin was associated with reduced progression of hand OA over time.…”
Section: Discussionmentioning
confidence: 82%
“…Weight loss is associated with reduction in these inflammatory adipokines (37). Furthermore, it is postulated that reduction in serum leptin is one mechanism by which weight loss improves physical function and symptoms in OA patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…62 The effects of weight loss and exercise interventions on serum leptin were also assessed in the ADAPT cohort. 63 In the ADAPT cohort, serum leptin was significantly reduced by a long-term diet (weight loss) intervention with modest weight loss of 5-6%. Serum leptin was also related to selfreported physical function with higher leptin concentrations related to greater impairments in physical function.…”
Section: Weight Reductionmentioning
confidence: 99%